Analysis of Determining Inpatient Room Rates Using the Activity-Based Costing Method in a Healthcare Setting: Analisis Penentuan Tarif Kamar Rawat Inap dengan Menggunakan Metode Activity-Based Costing di Lingkungan Pelayanan Kesehatan - Yuanis, Yuanis; Rahayu, Estri Purwani; Wasito, Wasito; Vizainiyah, Novi; Rahmawati, Elik; Aminah , Puji (Indonesian Journal of Innovation Studies, 2024)
Background: Hospitalization rate determination is crucial for healthcare cost management, yet traditional methods often lead to cost distortions. Specific Background: Muhammadiyah Tuban Hospital has historically utilized conventional costing methods, which have resulted in higher than necessary charges for hospital services. Knowledge Gap: There is limited research comparing traditional costing methods with more accurate and modern approaches like Activity Based Costing (ABC) in the Indonesian healthcare context. Aim: This study aims to compare hospitalization rates at Muhammadiyah Tuban Hospital using traditional methods and the ABC method, to highlight discrepancies and propose a more accurate costing framework. Results: The ABC method yielded significantly lower hospitalization rates across various classes (VIP, Class 1, Class 2, and Class 3) compared to traditional methods. For instance, the ABC rate for the VIP class was IDR 270,619, compared to IDR 495,000 set by traditional methods. Novelty: This study introduces the application of ABC in an Indonesian hospital setting, providing a clear contrast in cost-efficiency against traditional costing. Implications: The findings suggest that adopting the ABC method can lead to more precise and lower hospitalization rates, potentially reducing healthcare costs for patients and improving financial management within hospitals.Highlights: Cost Accuracy: ABC method offers more precise hospitalization rates than traditional methods. Economic Impact: Adoption of ABC can lower patient costs and improve hospital financial management. Innovation: Introduces a modern costing method to Indonesian healthcare, suggesting a shift from outdated practices. Keywords: Activity Based Costing, Hospitalization Rates, Cost Management, Healthcare Economics